Seismic Collapse Prevention of Non-Structural Infill Masonry Using eq-top: an Easy Earthquake Fibre Retrofitting System - KARAKALE, VAİL (SPRINGER HEIDELBERG, 2014)
Specially manufactured technical textile and polyurethane glue, called eq-top system is proposed to save life and prevent collapse of non-structural masonry, e.g. in filled walls during a seismic event with a minimum cost. The idea is to attach glass fiber textile on the brittle brick partition walls in the buildings and connect them with the peripheral structural frames. During an earthquake it is expected that the system will hold the non-structural elements in place and prevent their out of plan failures; also it will improve their in-plane stiffness making them working as structural infill walls. The proposed technical textile is light-weight, easy to handle, fast in application, and cheap compared to the well-known FRP and CRP. To test the eq-top system, shake table on full scale brick wall specimens was conducted at Bogazi double dagger i University in Turkey. The strengthened specimen and the non-strengthened specimens were fixed on the same shake table for a direct comparison and the amplitudes of base accelerations were increased until severe damage is reached in the non-strengthened and/or strengthened specimen. The seismic performance of the 2 x 2 specimens (two without and two with strengthening) was compared in terms of stiffness, strength, deformability and ductility. All thought that the specimens were excited under their resonance frequencies, no damage at all occurred in the strengthened specimen and total collapse happened already in the non-strengthened panel under low amplitudes. The results have confirmed effectiveness of the proposed retrofit scheme.
Keywords: Seismic; Buildings; Retrofitting; Masonry; Textile; Steel panel; Shake table; CFRP